Effects of Defense Suppliers’ Practice of Online Character Education on the Employees’ Learning Motivation and Perception of Integrity During COVID-19 - Hsiao, Hong-Chin (Frontiers in Psychology, 2021)
The 21st century marks a period where the pursuit of innovation, the advance of information media, and diverse values have gained great significance. In the face of information, economic impacts, and other challenges, developed countries in particular have come to emphasize online character education, as cultivating the people’s character to have a positive attitude toward life. Teaching people desirable core values and moral thinking to cultivate pleasant character could enhance personal happiness and social harmony, boost national competitiveness, and be the key to a more harmonious society in the future. Education is the stable rock of ethics and morality, and like the foundation upon which to build a house, an unstable rock would result in the danger of collapse. People’s sense of propriety, justice, integrity, and honor, as well as morality, is in decline. In such a social climate, online character education plays an extremely important role. Taking employees of defense suppliers for the Ministry of National Defense, Taiwan, as empirical subjects, 226 employees proceeded with our 20-week (4 h per week, for a total of 80 h) experimental teaching research. The research results reveal that: (1) online character education would affect learning motivation, (2) online character education would affect the perception of integrity, and (3) learning motivation presents significantly positive effects on the perception of integrity. Our results suggest that online character education and discussion is expected to help defense suppliers cultivate good social interaction skills and character to build harmonious interpersonal relationships.